Understanding perceptions of global healthcare experiences on provider values and practices in the USA: a qualitative study among global health physicians and program directors. Issue 4 (3rd April 2019) - Matthews-Trigg, Nathaniel; Citrin, David; Halliday, Scott; Acharya, Bibhav; Maru, Sheela; Bezruchka, Stephen; Maru, Duncan
Abstract : Objectives: The study aimed to qualitatively examine the perspectives of US-based physicians and academic global health programme leaders on how global health work shapes their viewpoints, values and healthcare practices back in the USA. Design: A prospective, qualitative exploratory study that employed online questionnaires and open-ended, semi-structured interviews with two participant groups: (1) global health physicians and (2) global health programme leaders affiliated with USA-based academic medical centres. Open coding procedures and thematic content analysis were used to analyse data and derive themes for discussion. Participants: 159 global health physicians and global health programme leaders at 25 academic medical institutions were invited via email to take a survey and participate in a follow-up interview. Twelve participants completed online questionnaires (7.5% response rate) and eight participants (four survey participants and four additionally recruited participants) participated in in-depth, in-person or phone semi-structured interviews. Results: Five themes emerged that highlight how global health physicians and academic global health programme leaders perceive global health work abroad in shaping USA-based medical practices: (1) a sense of improved patient rapport, particularly with low-income, refugee and immigrant patients, and improved and more engaged patient care; (2) reduced spending on healthcare services; (3) greater awareness of the social determinants of health; (4) deeper understanding of the USA's healthcare system compared with systems in other countries; and (5) a reinforcement of values that initially motivated physicians to pursue work in global health. Conclusions: A majority of participating global health physicians and programme leaders believed that international engagements improved patient care back in the USA. Participant responses relating to the five themes were contextualised by highlighting factors that simultaneously impinge on their ability to provide improved patient care, such as the social determinants of health, and the challenges of changing USA healthcare policy.